Spenser's legal language : law and poetry in early modern England - Zurcher, Andrew (Studies in Renaissance literature (Woodbridge, Suffolk, England), 2007)
This volume explores Spenser's linguistic experimentation and his engagement with political, and particularly legal, thought and language in his major works, demonstrating by thorough lexical analysis and illustrative readings how Spenser figured the nation both descriptively and prescriptively.